2021
DOI: 10.1186/s12969-021-00547-9
|View full text |Cite
|
Sign up to set email alerts
|

Is podocytopathy another image of renal affection in p-SLE?

Abstract: Background Lupus podocytopathy (LP) is a renal affection described in systemic lupus erythematosus (SLE) patients with nephrotic range proteinuria, characterized by diffuse foot process effacement without immune deposits and glomerular proliferation. This study describes LP, its pathological features and outcomes of pediatric (p-SLE) patients in comparison to the usual lupus nephritis (LN) cases. Methodology A retrospective cohort study conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 26 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…LP accounts for 1.33% of all LN biopsies in adults (9), representing 8.14% in children (21). Our data showed LP in <1% of all children with LN biopsies (unpublished).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…LP accounts for 1.33% of all LN biopsies in adults (9), representing 8.14% in children (21). Our data showed LP in <1% of all children with LN biopsies (unpublished).…”
Section: Discussionsupporting
confidence: 52%
“…To date, eleven pediatric cases of LP have been reported in PubMed. Four were case reports including our patient (Table 2), and a cohort study included seven patients (21)(22)(23)(24), which suggests that it is a very rare complication of SLE in children. All children with LP have been girls and present with NS (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the study by Hu et al [21] who examined adult cases of SLE, 50 out of 3750 (1.33%) renal biopsies met the definition of lupus podocytopathy. In the retrospective pediatric study by Abdelnabi et al, the incidence of lupus podocytopathy was found to be as high as 8.1% [23].…”
Section: Discussionmentioning
confidence: 95%
“…However, in rare instances, SLE patients with NS can have renal biopsy findings of normal appearing glomeruli, with or without mesangial proliferation, on light microscopy; the absence of subepithelial or subendothelial deposits on immunofluorescence and electron microscopy; and diffuse foot process effacement on electron microscopy. This pattern, termed LP, represents about 1% of LN biopsies [21,22]; however, one report found that about 8% of patients with pediatric LN may have LP [23].…”
Section: Discussionmentioning
confidence: 99%